Assessment of Teaching Creative Thinking in Primary School, a Study in Mathematics Subject - Nguyen Huu Chau (Research Developments in Arts and Social Studies Vol. 2, 2022)
Teaching thinking for students is an important task of education and it should be started at the primary level. In many primary schools, however, this task was not paid much attention. Since 2018 all primary schools in Vietnam have implemented the reformed curriculum, which emphasizes the importance of teaching creative thinking for students at all grades. This paper describes a practical study to analyze the current status and causes in teaching creative thinking for primary students. In order to view the current status of teaching creatvie thinking for last grades student in primary school the author conducted a survey at 6 primary schools in Thai Binh, Hanoi and Nam Dinh provinces in Vietnam with the participation of 145 primary teachers. Results of this survey showed that the ineffective development of creative thinking in primary schools is due to teacher’s unclear cognition of creative thinking development for students. Many teachers do not understand properly about the nature and characteristics of creative thinking of primary students and they also have no effective measures to conduct creative thinking education for students.